The Enactment of Strategic Leadership A Critical Perspective - Tipurić, Darko (Springer Nature, 2022)
This Open Access book explores the meaning and roles that strategy and leadership play in our lives. Based on decades of experience, the author contemplates whether we believe strategic leadership exists because it actually exists, or whether it exists because we believe it does? Both answers are true. The author argues that the duality of the essence of strategic leadership is clear. It may appear to be personalised, or it may seem to be an important characteristic of the organization enacted everywhere where there is guidance. In fact, the discussion about strategic leadership raises more questions. In this thought-provoking book, the author puts forward a robust critical assessment of one of the most widely used concepts in management research and practice. Beginning with an ontological and historical discussion around which the concept of strategic leadership has developed, the book continues to discuss the phenomenon of strategic leadership. Utilising a post-modern perspective and by heavily drawing on concepts such as hegemony and ideology, the author then discusses the role of organizational culture and networks, as well as the underlying tensions that come associated with strategic leadership.